Potential For Conversion Of Rice Fields For Farmers In Pendoworejo District, Kap. Girimulyo, Kab. Kulon Progo, Special Region of Yogyakarta - Ardhana, Bagas Pramudya; Fithriya, Dwi Nur Laela (Badan Penerbitan Fakultas Pertanian (BPFP), Universitas Bengkulu, 2023)
Pendoworejo Village, Kapanewon Girimulyo, Kab. Kulon Progo, DIY is an area designated by the government as LP2B (Sustainable Food Agricultural Land), but in reality, this area is experiencing quite a drastic shrinkage of agricultural land. This is influenced by the existing Trend “culinary with view” in the Kulon Progo area which is directly proportional to the widespread conversion of agricultural land into culinary business buildings. This phenomenon is a consequence of the modernization process in developing regions. This research aims to discover the social and economic impacts of local farmers in Pendoworejo District. To find answers to these problems, researchers used qualitative phenomenological research methods. The data obtained is primary data from interviews with informants who are farmers in Pendoworejo Village. This research shows that agricultural land conversion has the potential to have a social impact on local farmers in the form of reduced urbanization rates, changes in people's mindsets, cultural shock, and increasing affordability and availability of employment sectors. Meanwhile, the economic impact of agricultural land conversion is reducing unemployment, establishing relationships between entrepreneurs and the community, and increasing household income in local communities.